Les lunettes et la queue de blaireau : Jean Potocki et l’art du bien voyager - François Rosset (Viatica)
This article focuses on the work of the late 18th-century historian and scholar Jean Potocki, who travelled through many countries. His writings, which are characterised by their breadth, depth, diversity, and originality, allow for a reflection on the scriptural and documentary practices of travellers. Examining these visits to Spain, Turkey, Holland, Morocco, Lower Saxony, the Caucasus and China, the article identifies the specific features of Potocki’s prose: an art of the gaze, which he constantly adjusted, a constant availability, a discourse that is never overbearing.